UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATERI APRESIASI TERHADAP KEUNIKAN SENI MUSIK DAERAH SETEMPAT DENGAN MENGGUNAKAN MEDIA AUDIO VISUAL PADA SISWA KELAS VII A SMP NEGERI 3 RANDUDONGKAL - Muktinurasih, Rina (Jurnal Penelitian Pendidikan, 2014)
Folk music is an element of simplicity and regionalism. Improving activities toward the appreciation on the work of art, especially folk music, was carried out by identifying the variety of folk songs, according to the personal view of most students. Over the course of the years, most students can only enjoy music. Because it takes an interest in advance so that students can express the music. Music learningneeds a lot of practice, however most of the times teachers are dominating the classroom time allocation meanwhile the students do not have adequate time to practice. The problems addressed in this study are : (1) whether or not the use of Audio Visual media can improvestudents learning activity in folk music appreciation (2) whether or not the use ofAudio Visual media can improve students learning outcomes in folk music appreciation material. The method used in this study was classroom action research with two cycles, each cycle consists of 4 phases: (1) planning (2) implementation (3) observation/ evaluation, (4) reflection. The research results shows that there were improvements both in the students learning activities and outcome from the use of Audio Visual learning media in folk music appreciation material. During the pre cycle there were only 16 out of 34 students passed (47.07%), onthe first cycle there were 20 out of 34 students passed (74.24%), and finally onthe second cycle there were 28out of 34 students passed (82.35%). Therefore it can be concluded that by the end of this second cycle, the indicator of the overall success has achieved the required frequency.